(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Development of new optical probes is a promising trend that has been actively implemented in recent years. A rational design of the probes should consider a number of parameters that contribute to the ability of the probe to exhibit highly selective optical response to the analyte. The obvious criteria are the chemical stability and reactivity of the probe, its photostability and the possibility of its reusable application. In this work, new probes based on fused benzothiazoles with different heterocyclic substituents were studied. The spectrophotometric characteristics of compounds in dimethylsulfoxide, acetonitrile and ethanol solutions were obtained. The probes exhibited the absorption in the near UV region and the blue part of the visible spectrum. Absorption spectra of the molecules are characterized by broad band with absorption maximum around 391–400 nm. The selected compounds demonstrated a slight positive solvatochromism. The blue shift of absorption maxima is due to the formation of protonated form of the probe in the presence of hydrochloric acid. Further, in basic conditions, the absorbance maxima of the probes are localized at longer wavelength (Δλ around 80 nm). Reversibility of compounds in the reactions of deprotonation-protonation was studied. Formal protonation constants of compounds (lgKpf) in water-organic solutions were calculated using the UV-Vis spectrophotometry titration method. Protonation constants of probes are in the range: lgKpf = 2.67–4.95. The obtained values of the protonation constants are in good agreement with the data calculated using the software ACD Labs. The presence of the amidine fragment in the structure of the chromophore core leads to an increase in its basicity, with respect to heterocyclic substituents. It was shown that the presence of a substituent more basic than benzothiazole leads to the destruction of the probe in solution with a pH 11. It occurs due to the opening of the iminopyridine cycle into its synthetic precursor. Based on the results, 2-(1,3-benzothiazol-2-yl)-3-(3-hydroxypropyl)-1-imino-1H-pyrido[2,1-b][1,3]benzothiazole-4-carbonitrile was selected for further use as sensitive pH probe.